Noncontraceptive effects of combined oral contraceptives: benefits and risks of use - A L Unanyan; A D Nikonets; L N Aminova; V A Alimov; Yu V Chushkov; A V Shchukina; E A Kudrina; D V Baburin (IP Berlin A.V., 2017)
This publication is devoted to one of the most relevant areas of gynecological practice - the use of combined oral contraceptives (COCs), taking into account their positive non-contraceptive properties. The issue of how to use COCs with the benefit of reproductive health of women, with what to combine them and how to prevent the risks associated with taking hormonal drugs, is reflected in detail. The information is presented in the form of an analytical review of international studies on the benefits and risks of using COCs.